Severe Intraventricular Hemorrhage in Extremely Premature Infants: Are high Carbon Dioxide Pressure or Fluctuations the Culprit? - Altaany, Dima; Natarajan, Girija; Gupta, Dhruv; Zidan, Marwan; Chawla, Sanjay (American Journal of Perinatology, 2015)
Objective This study aims to examine the association between measures of hypercapnia and fluctuation in Pco2 and severe intraventricular hemorrhage (IVH) and to evaluate the prevalence of hypercapnia, hypocapnia, and fluctuations in Pco2 in the initial 72 hours of life among premature infants.Study Design Retrospective study of premature infants with birth weight < 1,250 g, who were receiving some respiratory support. All blood gases obtained in the first 3 days of life were collected. Univariate and multivariate analyses were performed to assess the association of hypercapnia, and fluctuations in Pco2 with severe IVH.Result Our cohort included 285 patients, of whom 84% were intubated. Only 20% patients had all blood gases in the normocapnia range; 9% had at least 1 gas with hypercapnia; 51% had at least 1 gas with hypocapnia, and 20% patients had both hypercapnia and hypocapnia at different times. Infants with severe IVH (n = 41) had significantly higher peak Pco2 and greater fluctuations in Pco2 within a short interval, compared with those without severe IVH (n = 227). After controlling for gestational age, gender, antenatal steroid exposure, presence of hypercapnia, and Apgar score at 5 minutes, fluctuation in Pco2 remained significantly associated with severe IVH.Conclusion Fluctuations in Pco2 within a short period may be more significantly associated with severe IVH than the mere presence of hypercapnia.
Keywords: intraventricular hemorrhage; hypercapnia; fluctuations in Pco2; carbon dioxide; premature infants; cerebral blood flow